Another look at the death of Rugby League in Vichy France. Issue 1 (2nd January 2023) - Rathbone, Keith
ABSTRACT: Since the 1990s, scholars interested in French Rugby League have argued that the Fédération française de rugby, France's Rugby Union organisation, and especially its honorary president Paul Voivenel, collaborated with a cabal inside the Vichy government to destroy their League rivals who had 'rebelled against the authority of French rugby'. Although the Vichy regime absolutely attacked Rugby League, the evidence for a conspiracy between Rugby Union federation and the state remains unsupported by any evidence. A rereading of the sources on Vichy's engagement with French Rugby League shows that their despoliation fell in line with other reforms undertaken by the French state at the same time. The Vichy French state undermined French Rugby League in line with their efforts to rationalise sports and maximise the number of athletes and contests across the metropole.